Actin-Binding Proteins and Disease - dos Remedios, Cris.; Chhabra, Deepak; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
This volume, written by experts in the field, is the first to deal with the relationship between human disease and the actin cytoskeleton. It provides overviews of actin and selected actin-binding proteins, and then focuses on diseases that involve these proteins. Specific chapters deal with actin, cofilin, profilin, gelsolin and thymosin ¾4. Other chapters discuss the roles of multiple actin-binding proteins in cancer and metastasis, leukocyte disorders, and heart failure, and there is a chapter that describes how intracellular pathogens use the host actin cytoskeleton. This seminal volume is intended for researchers, clinicians, physicians, and graduate students in the fields of biochemistry, cell biology, microbiology, immunology, and genetics.
Actin -- Actin: An Overview of Its Structure and Function -- Actin Genetic Diseases -- Actin-Binding Drugs: An Elegant Tool to Dissect Subcellular Processes in Endothelial and Cancer Cells -- Autoantigenicity of Actin -- Actin-Binding Proteins -- Overview: Actin-Binding Protein Function and Its Relation to Disease Pathology -- ADF/Cofilin, Actin Dynamics, and Disease -- Gelsolin and Disease -- Profilin -- The Roles of Thymosin ?4 in Cell Migration and Cell-to-Cell Signaling in Disease -- Actin-Binding Proteins -- Actin and Actin-Binding Proteins in Cancer Progression and Metastasis -- Diseases with Abnormal Actin and Actin-Binding Proteins in Leukocyte and Nonmuscle Cells -- The Role of PIP2 in Actin, Actin-Binding Proteins and Disease -- Intracellular Pathogens and the Actin Cytoskeleton -- Actin and Its Binding Proteins in Heart Failure.
Keywords: Cell biology; Proteomics; Proteins .; Biochemistry; Cell Biology; Proteomics; Protein Science; Biochemistry, general